Trend analysis of birth defects in Fengxian District, Shanghai, 2018‒2022 - MA Huihui; CHEN Hong; JIANG Hong; LIANG Guangsheng; HUANG Qin; QIN Meng (Shanghai yufang yixue)
ObjectiveTo retrospectively analyze the epidemiological trends of birth defects in perinatal infants in Fengxian District, Shanghai from 2018 to 2022, so as to provide a scientific evidence for the formulation of related prevention and control strategies.MethodsBased on the data from the National Birth Defects Surveillance System, statistical analysis was conducted on the perinatal birth defects from monitored hospitals within the region from 2018 to 2022.ResultsFrom 2018 to 2022, a total of 20 870 perinatal infants delivered in the monitored hospitals in Fengxian District, with 472 cases with birth defects, showing a significant increase in the prevalence of birth defects (PRR=1.49, 95%CI: 1.39‒1.59). The risk of birth defects increased with maternal age, especially for advanced maternal age (PRR=1.58, 95%CI: 1.12‒2.25). Infants born to mothers with gestational diabetes had a higher prevalence of birth defects compared to those without gestational diabetes (PRR=1.99, 95%CI: 1.46‒2.70). Infants with birth defects were more likely to be born prematurely (PRR=2.07, 95%CI:1.56‒2.76). The top three types of birth defects were congenital heart disease (CHD), other anomalies of the external ear, and polydactyly.ConclusionThe prevalence of birth defects in Fengxian District monitored hospitals showed an upward trend from 2018 to 2022. Advanced maternal age and gestational diabetes were identified as risk factors for birth defects. CHD is the leading type of birth defect in Fengxian District over the five-year period. To reduce the prevalence of birth defects, it is crucial to implement comprehensive prevention and treatment measures for CHD.